(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2024)
This essay is a reflection on the field of Social and Solidarity Economy as a variant of Latin American economic thought, heterogeneous and pluralistic, which represents one of the critical synthesis of contemporary thought together with ecological economics and feminist economics. This enabled elements to deconstruct and interpret the socioeconomic processes historically constituted in specific spaces and times, being conceived as a theoretical perspective around the micro and meso-socioeconomic with a strong operational character in terms of its political dimension. A theoretical and practical perspective that democratizes knowledge embedded in territories that dialogue and respond to what De Sousa Santos (2009) calls the ecology of knowledge.